EFFICIENCY OF MSME INVESTMENT THROUGH INTEGRATION OF RESOURCE ALLOCATION AND ENVIRONMENTAL SCANNING USING A BUSINESS STRATEGY ANALYSIS APPROACH - Fajri, Mega Barokatul; Muhammad, Mohd Zulkifli; Nordin, Nurhaiza (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
In today’s uncertain economic conditions, achieving investment efficiency is a significant challenge for MSMEs, especially those with limited resources and high uncertainty in the business environment. This research aims to explore and analyze how resource allocation and environmental scanning are integrated in MSMEs in the food and beverage sector in Lamongan Regency, Indonesia, to achieve investment efficiency. The design of this study uses exploratory qualitative research with purposive sampling and snowball sampling techniques as sampling techniques. The results of this study show that investment efficiency is greatly influenced by the decisions of actors in setting resource allocation priorities and environmental conditions as reflected in the implementation of BMC, PESTEL Analysis, Porter's Five Forces, and Value Chain analysis. MSMEs that actively monitor market trends, consumer preferences, and cost fluctuations can indirectly allocate their resources, such as capital, labor, time, and managerial capacity, strategically to minimize investment risk and improve business performance. Conversely, MSMEs whose business activities depend on intuition without conducting significant environmental scanning can create investment inefficiencies. This study confirms that integrating MSME resource allocation with environmental scanning can improve investment efficiency and maintain business environment flexibility.